Ben Okri's The famished road: a case study in the translation of New Englishes - Ngam, Roland Nkwain (My University, 2008)
Abstract This dissertation suggests a new approach to the translation of African literature, and more precisely African literature in English, considering that the English language has evolved. In most former colonies, New Englishes exist alongside standard varieties of English. This linguistic trend needs to be accompanied by well thought out and researched strategies, if translations are to match the success of the original versions. As a first step, the research report engages with a definition of New Englishes as well as of other important concepts in the research report: colonialism, post-colonialism, negritude, translation, nativisation and indigenisation. Examples of New Englishes are established through an analysis of The Famished Road. This is followed by a discussion of translation theory, with special focus on dynamic equivalence and functionalism. Finally, recommendations are made in relation to methods and strategies for translating a West African novel from English to French.
Keywords: The Famished Road; New Englishes; translation